Misdiagnosis and mistreatment of a common side‐effect – angiotensin‐converting enzyme inhibitor‐induced cough - Vegter, Stefan; De Jong‐van den Berg, Lolkje T. W. (British journal of clinical pharmacology, 2010)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Dry cough is a common and well‐documented side‐effect of angiotensin‐converting enzyme inhibitor (ACEi) treatment. • The recommended course of action in case of ACE‐induced cough is substitution of the ACEi with other antihypertensive agents. • Misdiagnosis and mistreatment of ACEi‐induced cough has not been studied before. WHAT THIS STUDY ADDS • In the general population, a significant and clinically relevant proportion of patients with ACE‐induced cough are treated with antitussive agents. • These results suggest misdiagnosis and mistreatment of a well‐known side‐effect. • The estimated frequency of antitussive treatment of ACEi‐induced cough is 15%. AIMS Angiotensin‐converting enzyme inhibitors (ACEi) are frequently prescribed for various cardiovascular and renal diseases. A common side‐effect of these drugs is a persistent dry cough. Physicians who fail to recognize a dry cough to be ACEi‐related may attempt to treat it with antitussive agents instead of recommended ACEi substitution. Prescription behaviour in the general population considering treatment of the side‐effect with antitussive agents has not been studied before. METHODS Drug dispensing data between 2000 and 2007 were retrieved from the IADB.nl database. A prescription sequence symmetry analysis was used to determine whether antitussive agents were prescribed more often following ACEi initiation than the other way around. A logistic regression model was fitted to determine predictors. RESULTS We identified 27 446 incident users of ACEi therapy. One thousand and fifty‐four patients were incident users of both ACEi and antitussives within a half‐year time span. There was an excess of patients being prescribed antitussive agents after ACEi initiation (703 vs. 351), adjusted sequence ratio 2.2 [confidence interval (CI) 1.9, 2.4]. Female patients were more likely to be prescribed antitussive agents following ACEi therapy initiation, odds ratio 1.4 (CI 1.1, 1.9), age and co‐medications were not significant predictors. CONCLUSIONS There was a significant and clinically relevant excess of patients receiving antitussives after ACEi initiation. The results suggest that cough as a side‐effect of ACEi is not recognized as being ACEi‐related or is symptomatically treated with antitussive agents instead of ACEi substitution. The estimated frequency of antitussive treatment of ACEi‐induced dry cough is 15%.